2008
DOI: 10.1021/je7005067
|View full text |Cite
|
Sign up to set email alerts
|

Vapor Pressure and Enthalpy of Vaporization of Fentanyl

Abstract: This paper describes the application of thermogravimetry including conventional thermobalance and standard sample holders for the estimation of vapor pressure and related thermodynamic properties of a potent narcotic analgesic, fentanyl . For this study, benzoic acid was used as a reference material to calibrate the thermogravimetric analysis (TGA) instrument and experimental conditions used. The relationship between the isothermal sublimation rates of benzoic acid determined at different temperatures and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…The consistency of the vapor pressure results above the liquid (melted) substance measured by a thermobalance subjected to isothermal and nonisothermal conditions under a flowing inert gas atmosphere was tested in our previous vaporization studies on pesticides using recommended reference compounds (i.e., benzoic acid [4,11], succinic acid and salicylic acid [4], acetanilide [5] and ferrocene [7]). Extension of vapor pressure measurements above the solid using a more classical weighing torsion effusion technique [5,6,19] as well as the extensive use of TG reported in literature [11,[20][21][22][23][24] in deriving vapor pressure data demonstrated the methods reliability (at least in the pressure range between about 10 and 10 3 Pa).…”
Section: Isothermal and Nonisothermal Thermogravimetry Measurements Omentioning
confidence: 99%
See 1 more Smart Citation
“…The consistency of the vapor pressure results above the liquid (melted) substance measured by a thermobalance subjected to isothermal and nonisothermal conditions under a flowing inert gas atmosphere was tested in our previous vaporization studies on pesticides using recommended reference compounds (i.e., benzoic acid [4,11], succinic acid and salicylic acid [4], acetanilide [5] and ferrocene [7]). Extension of vapor pressure measurements above the solid using a more classical weighing torsion effusion technique [5,6,19] as well as the extensive use of TG reported in literature [11,[20][21][22][23][24] in deriving vapor pressure data demonstrated the methods reliability (at least in the pressure range between about 10 and 10 3 Pa).…”
Section: Isothermal and Nonisothermal Thermogravimetry Measurements Omentioning
confidence: 99%
“…Gupta et al [11] demonstrated the reliability of TG to determine vapor pressure and enthalpy of vaporization of a drug, using the same procedure adopted in [10]. By contrast, some authors [12,13] proposed revised vaporization equations justified by the fact that the rate of vaporization is limited by diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…The vapor pressure of fentanyl is very low (4.6 × 10 -6 Pa) suggesting that evaporation of standing product into a gaseous phase is not a practical concern [18].…”
Section: Inhalation Exposure Risk For Fentanyl and Fentanyl Analogsmentioning
confidence: 99%
“…In this field of study, it is also typical to calculate the vapor pressure from rate constant values using the Langmuir equation and then to fit the obtained values according to the Clausius-Clapeyron equation to find the standard enthalpy values. For example, Gupta et al [18] calculated vapor pressure from constant rates and determined sublimation enthalpy of fentanyl and TATP, respectively, using the Clausius-Clapeyron linear equation [13][14][15][16][17][18][19]. On the other hand, other authors have combined spectroscopic and thermal techniques to study physical and chemical properties of different materials [20][21][22].…”
Section: Introductionmentioning
confidence: 99%